Experimental study of Rac1 regulating osteoclast function in hypoxic environment - GU Jiahong; TIAN Yuanye; KANG Feiwu (Kouqiang hemian waike zazhi)
[Objective:] To investigate the effect of hypoxia-inducible factor-1α (HIF-1α) on the changes of osteoclast bone resorption capacity by regulating Rac1 on cytoskeleton under hypoxic environment. [Methods:] The hypoxia culture system was established by stimulating mouse mononuclear cell line RAW264.7 with cobalt dichloride (CoCl2) in vitro. The differentiation of RAW264.7 cells was induced by sRANKL conditioned culture medium and stimulated by CoCl2 simulated hypoxic environment, and TRAP staining was performed after 7 days; real-time quantitative polymerase chain reaction (RT-qPCR), cellular immunofluorescence assay and Western blotting were used to detect the expression of HIF-1α KO Rac1, osteoclast-related surface markers and closure zones in RAW264.7 under hypoxia. Simultaneously, HIF-1α conditional knockout cell line RAW264.7 and the effect of the inhibitor of Rac1 on the expression of osteoclast-related genes and closure zones in RAW264.7 under the same conditions were detected. [Results:] Hypoxia could increase the volume of RAW264.7 induced osteoclasts and enhance bone resorption capacity (P<0.01). The level of Rac1 mRNA expressed by osteoclasts in hypoxia group was increased, and the expression of closure zones were significant (P<0.001). The volume of osteoclasts induced by HIF-1α KO RAW264.7 cells decreased, the expression of HIF-1α was significantly decreased, and Rac1 was also decreased (P<0.001); meanwhile, the volume of osteoclasts decreased in the inhibitor group, the expression of HIF-1α remained unchanged, and the closure zones formed abnormally (P<0.01). [Conclusion:] Under hypoxia, mouse mononuclear cell line RAW264.7 can regulate Rac1 through HIF-1α protein to affect the cytoskeleton of osteoclasts, and then change the bone resorption capacity of osteoclasts.